Pelatihan Akuntansi Kepada Ibu-ibu Rumah Tangga di Desa Kelambir Lima Kebon - Anita Putri; Hartato Rianto (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
This article describes the complex implementation of Community Service (PKM) carried out in Kelambir Lima Kebun Village, where PKM activities are carried out to overcome the problems experienced by housewives in managing their finances. This PKM presents a solution to the problem by providing accounting training. The training was conducted using two methods, namely lectures and simulations. This is done to maintain the effectiveness of PKM so that the objectives can be achieved. The results of this community service are considered quite effective in overcoming the problems experienced by housewives, although there are still some PKM participants who do not apply the knowledge gained during PKM so that they do not experience significant changes in managing their finances. It is suggested that the next PKM should not only focus on the quality of increasing the knowledge or skills of the participants but also be able to instill motivation to realise the knowledge or skills in daily life.